The unmaking of June Farrow : a novel [large type] - Young, Adrienne, 1985- (Thorndike Press large print dynamic drama., 2024)
"In the small mountain town of Jasper, North Carolina, June Farrow is waiting for fate to find her. The Farrow women are known for their thriving flower farm--and the mysterious curse that has plagued their family line. The whole town remembers the madness that led to Susanna Farrow's disappearance, leaving June to be raised by her grandmother and haunted by rumors. It's been a year since June started seeing and hearing things that weren't there. Faint wind chimes, a voice calling her name, and a mysterious door appearing out of nowhere--the signs of what June always knew was coming. But June is determined to end the curse once and for all, even if she must sacrifice finding love and having a family of her own. After her grandmother's death, June discovers a series of cryptic clues regarding her mother's decades-old disappearance, except they only lead to more questions. But could the door she once assumed was a hallucination be the answer she's been searching for? The next time it appears, June realizes she can touch it and walk past the threshold. And when she does, she embarks on a journey that will not only change both the past and the future, but also uncover the lingering mysteries of her small town and entangle her heart in an epic star-crossed love. With The Unmaking of June Farrow, Adrienne Young delivers a brilliant novel of romance, mystery, and a touch of the impossible--a story you will never forget"--